Efficacy and safety of low-dose esketamine for painless gastrointestinal endoscopy in adults: a systematic evaluation and meta-analysis - Deng, Juan; Yu, Yun-Feng; Tang, Zheng-Guo; Lei, Hua-Juan; Tan, Chuan-Chuan (Frontiers in Pharmacology, 2024)
Object: The benefits of low-dose esketamine for painless gastrointestinal endoscopy remain unclear. As such, the present study aimed to investigate the efficacy and safety of low-dose esketamine for this procedure. Methods: Seven common databases were searched for clinical studies investigating low-dose esketamine for painless gastrointestinal endoscopy. Subsequently, a meta-analysis was performed to synthesize and analyze the data extracted from studies fulfilling the inclusion criteria. Results: Meta-analysis revealed that, compared with propofol, low-dose esketamine in combination with propofol significantly reduced recovery time by 0.56 min (mean difference [MD] −0.56%, 95% confidence interval (CI) −1.08 to −0.05, p = 0.03), induction time by 9.84 s (MD −9.84, 95% CI −12.93 to −6.75, p < 0.00001), propofol dosage by 51.05 mg (MD −51.05, 95% CI −81.53 to −20.57, p = 0.01), and increased mean arterial pressure by 6.23 mmHg (MD 6.23, 95% CI 1.37 to 11.08, p = 0.01). Meanwhile, low-dose esketamine reduced injection pain by 63% (relative risk [RR] 0.37, 95% CI 0.28 to 0.49, p < 0.00001), involuntary movements by 40% (RR 0.60, 95% Cl 0.42 to 0.85, p < 0.005), choking by 42% (RR 0.58, 95% Cl 0.38 to 0.88, p = 0.01), bradycardia by 68% (RR 0.32, 95% Cl 0.18 to 0.58, p = 0.0002), hypotension by 71% (RR 0.29, 95% Cl 0.21 to 0.40, p < 0.00001), respiratory depression by 63% (RR 0.37, 95% 0.26 to 0.51, p < 0.00001), additional cases of propofol by 53% (RR 0.47, 95% Cl 0.29 to 0.77, p = 0.002), and increased hypertension by 1000% (RR 11.00, 95% Cl 1.45 to 83.28, p = 0.02). There were no significant differences in mean heart rate, mean oximetry saturation, delirium, dizziness, vomiting, tachycardia, and hypoxemia. Subgroup analyses revealed that, compared with other dose groups, 0.25 mg/kg esketamine afforded additional benefits in recovery and induction time, mean arterial pressure, involuntary movements, hypoxemia, and respiratory depression. Conclusion: Low-dose esketamine was found to be safe and effective for providing anesthesia during gastrointestinal endoscopy, with 0.25 mg/kg identified as the optimal dose within the dosage ranges examined. However, caution should be exercised when administering this drug to patients with inadequate preoperative blood pressure control.